THE BEHAVIOR OF MIXED CA-MN CARBONATES IN WATER AND SEAWATER: CONTROLS OF MANGANESE CONCENTRATIONS IN MARINE POREWATERS - Mucci A. (My University, 2004)
The dissolution behavior of natural, ordered kutnahorite (Mn1.14Ca0.82Mg0.04Fe0.012(CO3)2) and a disordered, calcian rhodochrosite (Mn1.16Ca0.78Mg0.06(CO3)2) precipitated in the laboratory was investigated in deionized distilled water and artificial seawater in both open and closed systems at 25 C, one atmosphere total pressure, and various pCO2s. Both solids dissolved congruently in distilled water in an open system and yielded identical long-term equilibration or extrapolated ion activity products, IAPpkt = aCa 2+aMn 2+(aCO 3 2–)2 = 1.7 (0.12) 10–21 or pIAPpkt = 20.77 (0.03). This value is believed to be the thermodynamic solubility product of pseudokutnahorite. In contrast, the steady state ion concentration products, ICPpkt = [Ca2+][Mn2+][CO3 2–]2, measured following the dissolution of both minerals in artificial seawater increase as the CO2 partial pressure decreases and the [Mn2+]:[Ca2+] ratio increases. These observations are interpreted as resulting from the formation of phases of different stoichiometry in response to large variations of the [Mn2+]:[Ca2+] ratio in solution. These data and results of calcite-seawater equilibration experiments in the presence of various dissolved Mn(II) concentrations define the fields of stability of manganoan calcites and calcian rhodochrosites in seawater within Lippmann phase diagrams for the CaCO3–MnCO3–H2O system. Results of this study reveal that the nature (i.e., mineralogy) and composition of manganese-rich carbonate phases that may form under suboxic/anoxic conditions in marine sediments are dictated by the porewater [Mn2+]:[Ca2+] ratio, the abundance of calcite surfaces and reaction kinetics.
Keywords: solubility; seawater; solid solutions; pseudokutnahorite; manganoan calcite; calcian rhodochrosite